DStudy on small interference analysis and transmission capacity of UHVAC loop power grid of Shandong–Hebei. Issue 2 (February 2021) - Gao, Yu; Xiong, Zaibao; Du, Shaofei; Geng, Xiaohong; Tian, Yingtao; Li, Yunpeng
Abstract: This paper studies the main operation characteristics, small interference analysis and transmission capacity of UHVAC in Shandong- Hebei loop power grid. It mainly includes the small interference characteristics and section transmission limit analysis of the certain area under the typical mode and maintenance mode, then the operation limit would be defined, so as to provide basic work for the safety and stability calculation of the loop network in the next stage.